Frequency of Food Shopping and Fruit and Vegetable Consumption: A Systematic Review - Kopetsky, Amanda (Curr Dev Nutr, 2020)
OBJECTIVES: To examine the relationship between frequency of food shopping and fruit and vegetable (FV) intake in adults. METHODS: A systematic review, guided by the Cochrane handbook, was conducted across four online databases: PudMed, CINAHL, Web of Science and the Cochrane Library. Studies were included if published in a peer reviewed journal through March 2019, included adults (³ 18 years of age), and were conducted in the United States. Any study using a cross-sectional, longitudinal cohort, or randomized study design that examined the relationship between the exposure variable of frequency of food shopping (defined as purchasing foods at a grocery store, farmer's market, corner store, convenience store, specialty store, mobile produce van) and outcome variable, FV intake was selected. Study quality was reviewed using the Quality Control Checklist. Due to heterogeneity across study designs and variable measurement, the systematic review findings were qualitatively summarized. RESULTS: A total of 1021 records were reviewed after 488 duplicates were removed and 69 were selected for full review. Twenty met inclusion criteria and were included in the systematic review. The majority of studies (75%) found evidence of a positive association between the frequency of food shopping and FV intake, such that as frequency increased so did FV intake. The majority of studies received a neutral rating for study quality as most studies (85%) had a cross-sectional or longitudinal design and lacked a consistent definition of frequency of food shopping. FV intake was assessed using self-report measures with only one study using 24-hour recalls. CONCLUSIONS: There is evidence to show a positive relationship between frequency of food shopping and increased FV intake. More frequent shopping may be an important strategy to incorporate as part of nutrition education, especially within food assistance programs as it may promote FV intake. Given food shopping frequency was broadly defined across food store types that were variable, future research should consider examining if store type influences FV intake. FUNDING SOURCES: None.